Globalization : a very short introduction - Steger, Manfred B., 1961- (Very short introductions, 2003)
This work offers a stimulating introduction to globalisation and its varying impacts across, between, and within societies. It is a readable book that contributes to a better understanding of the crucial aspects and dimensions of the developments and transformations that go by the name of globalisation.